The Influence of Intellectual Capital on Financial Performance with Earnings Management as A Mediating Variable in Financial Companies Listed on The IDX in 2020-2022 - Wasista, I Gede Pande Eka; Pradnyani, Ni Luh Putu Sri Purnama; Wasita, Putu Aristya Adi (Pertapsi-Indonesia collaborated with Petra Christian University, 2024)
Financial performance is a form of evaluation and analysis of the financial performance of an entity in achieving its objectives. To achieve good financial performance, of course, quality resources are needed. Intellectual capital can be the main reason for achieving good financial performance in an entity because it has competitive advantages such as knowledge, skills, experience, and adequate information, which is in line with the resource-based view theory. However, to achieve good financial performance in the eyes of the public, earnings management practices are often carried out in each entity to cover up failures or fulfill the wishes of stakeholders. Earnings management practices are acts of manipulation of an entity's financial data to make it look good in the eyes of the public and do not describe actual financial performance. This research was conducted on insurance sub-sector financial companies listed on the IDX in 2020–2022. The method of determining the sample used was purposive sampling with the criteria that the insurance sub-sector financial companies published their annual reports consecutively from 2020–2022, so that 11 insurance sub-sector financial companies were obtained. The data analysis techniques used are SEM-PLS and path analysis using the SmartPLS application. Based on the research results, it is known that intellectual capital proxied using VAIC has a positive effect on financial performance proxied by ROA. Intellectual capital proxied by VAIC has no effect on earnings management proxied by DAC. Earnings management, proxied by DAC, has no effect on financial performance, proxied by ROA. Intellectual capital has no effect on financial performance after being mediated by earnings management; therefore, earnings management is called full mediation.